Manajemen Pelatihan Coorporate Social Responsibility (CSR) di Coorporate Forum For Comunity Development (CFCD) Jakarta - Nur Lis Aviani; Siti Zulaikha; Wahyu Sri Ambar Arum (Program Studi Manajemen Pendidikan, 2016)
This research was conducted at the Division of Training Coorporate Forum For Comunity Development, Jakarta, which aim to identify CSR training management process. This research was conducted on April 2015 to January 2016. This research used qualitative approach with descriptive methode. Data was collected through interview, observation and documentation study. Data sources was gained from Managing Director, Training Manager, Managing Secretary, and several supported informants such as Training Manager Assistant, Training Instructor and CSR Training Participant.Planning of CSR training was conducted by analyzing training needs, arrange curriculum, materials, teaching materials, schedule and organizing recruitment of participants and instructor. While the implementation of training activities carried out through two stages including basic training dan advance training. Evaluation was held by asessing the organizers, training program, materials, instructor, facilities and training participants through four ways to measurereaction,learning, behavior and result.Training Division should be more active and cooperative while planning a training schedule, and give socialization and publication about the importance of CSR training baed on ISO 26000 as much as possibe, altering group discussion formation in order to give encouragement for passive participants to become more active, Reminding participants anymore about the importance of filling evaluation form, establishing cooperation with government and stakeholder to achieve prosperity of civil society by conducting CSR program based on ISO 26000